Amelanotic Melanoma Arising in Surgical Cicatrix: A Case Report - Norling, Anna Louise; Brøchner, Christian Beltoft; Langhans, Linnea (Case reports in dermatology, 2025)
Introduction: Amelanotic melanoma (AM) is a rare subtype of melanoma characterized by the absence of pigmentation, making it difficult to diagnose. This case report describes AM arising in a cicatrix following cardiac surgery, highlighting diagnostic challenges and the importance of reassessment when the clinical findings do not fit the initial diagnosis. Case Presentation: A 76-year-old male underwent coronary artery bypass grafting in March 2022. Nine months later, he noticed a mass with ulceration in the sternal cicatrix. A punch biopsy showed inflammation and fibrosis, leading to a diagnosis of suture granuloma. Despite the lesion’s progression over 8 months, no further biopsies or treatments were performed. In September 2023, the patient was referred to the Department of Plastic Surgery at Copenhagen University Hospital, Rigshospitalet, where an excision biopsy revealed an AM with a thickness of 20 mm. Preoperative PET-CT showed no evidence of metastasis, and re-excision with sentinel lymph node biopsy was performed. Adjuvant oncologic treatment was administered due to a positive sentinel node. Conclusion: This case emphasizes the diagnostic challenges of AM, especially when arising in a cicatrix. When the clinical picture does not align with the initial diagnosis, it is crucial to reconsider and conduct further evaluations to avoid delays in treatment.